PARTISIPASI MASYARAKAT DALAM PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN PESISIR KECAMATAN LIMAPULUH KOTA PEKANBARU - Irvan, Hafidzita Eka Putri; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The city without Slums programme (KOTAKU) is a program that funded nationally in 271 counties/cities in 34 provinces that became a collaboration platform or base of the handling of the slums that integrate various resources and funding sources , including those from the Central Government, provinces, counties or cities, donors, private, public, and other stakeholders. Coastal village is one of the implementing kotaku, goals of the research is to describe and analyse the forms of community participation. The methods used in this research was the qualitative approach. Data collection techniques used are interviews, observation and documentation. The results showed that this form of public participation was seen from public participation in decision making, participation in the implementation phase, the participation in the taking of benefits, and the participation of the community in stages of the evaluation. Based on the foregoing indicates that public participation is already there but not thorough all phases. Because there are still constraints that impede public participation ranging from low levels of public awareness, weak understanding of the people and the bustle of the community. Then it is necessary to approach the community so the community understands the purpose of the program that implemented and communication between stakeholders, community and village apparatus must be maintained so that there is no misunderstanding.Keywords: Public Participation, Development, Community Empowerment, Program Cities Without Slums (KOTAKU)